2014
DOI: 10.1177/1077559514548316
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Using Medicaid Claims to Ascertain Child Maltreatment

Abstract: Medicaid data contain International Classification of Diseases, Clinical Modification (ICD-9-CM) codes indicating maltreatment, yet there is a little information on how valid these codes are for the purposes of identifying maltreatment from health, as opposed to child welfare, data. This study assessed the validity of Medicaid codes in identifying maltreatment. Participants (n = 2,136) in the first National Survey of Child and Adolescent Well-Being were linked to their Medicaid claims obtained from 36 states. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Although ascertainment of child maltreatment via administrative claims is challenging, it has been noted as a major confounder for obesity at this age (Raghavan et al, 2015; Shin & Miller, 2012). We selected child maltreatment ICD-9 codes from a recent child maltreatment study (Raghavan et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ascertainment of child maltreatment via administrative claims is challenging, it has been noted as a major confounder for obesity at this age (Raghavan et al, 2015; Shin & Miller, 2012). We selected child maltreatment ICD-9 codes from a recent child maltreatment study (Raghavan et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Although ascertainment of child maltreatment via administrative claims is challenging, it has been noted as a major confounder for obesity at this age (Raghavan et al, 2015; Shin & Miller, 2012). We selected child maltreatment ICD-9 codes from a recent child maltreatment study (Raghavan et al, 2015). The indicator variable included ICD-9 diagnostic codes for the following conditions: child maltreatment (995.5), effects of hunger or thirst (994.2 or 994.3), personal history of psychological trauma presenting hazards to health (V15.4), counseling for victim of child abuse (V61.21), observation and evaluation for suspected abuse and neglect (V71.81), rape or alleged rape/seduction (E906.1 or V71.5), criminal neglect (E968.4), assault (E961-E966, E968), or no food/no water (E904.1 or E904.2).…”
Section: Methodsmentioning
confidence: 99%
“…Pediatricians underestimate the rates of maltreated children in their practice 9 and typically do not screen for ACEs, which include maltreatment. 10 Studies comparing documentation rates with maltreatment rates confirmed through other means, such as interdisciplinary review teams, 11-13 caseworker determinations, 14 and independent review of medical records, 15 have demonstrated that most children with confirmed maltreatment are not assigned maltreatment-related codes in medical settings in the United States. Researchers from Taiwan, 16 Australia, 17 and the United Kingdom 18 also report underdocumentation of maltreatment relative to other means of estimating maltreatment rates.…”
mentioning
confidence: 99%
“…11,13,15 Although some studies suggest that maltreatment is less likely to be ascertained 11,15,26 and reported 19,27 for Whites than Blacks, other studies suggest that Black children with confirmed maltreatment are less likely to be assigned an ICD maltreatment code than Whites. 14…”
mentioning
confidence: 99%
“…Reported cases could be supplemented with administrative health data, such as hospital records (McKenzie, Scott, Frazer, & Dunne, 2012), Medicaid claims (Raghavan, Brown, Allaire, Garfield, Ross, & Hedeker, 2015), or vital statistics (Putnam-Hornstein, Webster, Needell, & Magruder, 2011). For example, in an Australian sample, McKenzie and colleagues (2012) found that about 1 in 15 children had hospital codes for maltreatment but could not be linked to CPS data, highlighting the potential contribution of hospital-based data to identify previously unreported victims.…”
Section: Data Sourcesmentioning
confidence: 99%